CLASSROOM MANAGEMENT IN IMPROVING SCHOOL LEARNING PROCESSES IN THE CLUSTER 2 TEACHER WORKING GROUP IN NORTH BOGOR CITY - Setyaningsih, Sri; Suchyadi, Yudhie (UNIVERSITAS PAKUAN, 2021)
The purpose of this research is to describe the planning of classroom management, the implementation of classroom management, supporting and inhibiting factors of classroom management to increase the learning process, and then the strategy to increase the learning process. The research methodology is a descriptive qualitative method. The result showed that the planning of classroom management do with prepared and arrange a set of equipment and instruments of study. The implementation of classroom management in the study applied some classroom management principles and some approaches. The supporting and inhibiting factors are physical environments, social-emotional, and organizational conditions. The strategy was student's condition for already studying in the class, learn to concentrate, using the right method and variation, interaction in educative and communicative, and then the students were using media with the teaching was.